Do domestic firms benefit from foreign presence and competition in Irish services sectors? - Stefanie A. Hallery (The Economic and Social Research Institute (ESRI), 2011)
This paper examines whether local firms benefit from the presence of foreign-owned firms in three Irish market-services sectors between 2001 and 2007. I investigate whether domestic firms differ in their ability to benefit from foreign presence using three different measures of absorptive capacity and also whether the foreign subsidiaries differ in their ability to generate spillovers. To account for the difficulty of productivity measurement in services, turnover-based, value-added-based and input-based productivity measures are employed. I find weak evidence of positive spillovers to domestic non-importers in the transport, storage and communication sector. In wholesale and retail trade, foreign presence is associated with lower capital-labour ratios and higher part-time-to-full-time employee ratios among domestic firms. In contrast, import competition is associated with higher productivity of the domestic firms in the transport, storage and communication and the business activities sector.
Keywords: F23; O33; L80; 330; foreign direct investment; absorptive capacity; services; productivity spillovers